Veni vidi VC – the backend of the digital economy and its political making - Franziska Cooiman (Review of International Political Economy, 2021)
Debates on the digital economy neglect its political and financial underpinnings. This article develops the theoretical framework of governing along the investment chain to grasp the backend of the digital economy, that is venture capital and its political underpinnings. Concretely, I focus on the European Investment Fund and how the European Commission uses it to govern along the investment chain into the digital economy. Therefore I conceptualize venture capital from a political economy perspective, situate the European Investment Fund in the European polity, and analyze transformations in the shape of the investment chains, risk-return distribution, and infrastructural power in three distinct periods. I show how in acts of crisis-led institutional innovation, the European Investment Fund has taken a central position in European venture capital investment chains, while skewing the risk-return relationship towards private markets and granting infrastructural power to venture capital funds. This dynamic inhibits the European Investment Fund from taking a progressive and proactive role in European venture capital markets.
Keywords: 330; venture capital; digital economy; EIF; financialization; investment chains; EU